Multi Container on Docker as a Support for IoT-Based Blockchain Electronic Transaction Systems - FIRMANSYAH, MUHAMMAD HAFIDH; Utoyo, Deva Baskara; Irnanda, Mohammad; Permana, Muhammad Fajarsyah Eka; Nandito, Gusti Arliz (Pusat Riset dan Inovasi Nasional, 2024)
The use of blockchain as a supporting element in securing transactions is growing, as the presence of the blockchain system ensures enhanced security in the data transaction process. However, it should be noted that blockchain requires a more complex system for data verification. This complexity is not a concern when using paid blockchain services. However, when users aim to implement it privately, multiple nodes are needed for transaction verification. We present a proposed scheme for the use of multiple nodes utilizing Docker for transaction verification. This approach makes the costs more affordable and the maintenance easier.